Climate change, grazing, and collecting accelerate habitat contraction in an endangered primate. (March 2019) - Zhao, Xumao; Ren, Baoping; Li, Dayong; Garber, Paul A.; Zhu, Pingfen; Xiang, Zuofu; Grueter, Cyril C.; Liu, Zhijin; Li, Ming
Abstract: Correlational models are widely used to predict changes in species' distribution, but generally have failed to address the comprehensive effects of anthropogenic activities, climate change, habitat connectivity and gene flow on wildlife sustainability. Here, we used integrated approaches (MAXENT model, circuit model and genetic analysis) to assess and predict the effects of climate change and anthropogenic activities on the distribution, habitat connectivity, and genetic diversity of an endangered primate, Rhinopithecus bieti, from 2000 to 2050. We created six scenarios: climatic factors only (scenario-a), anthropogenic activities only (scenario-b), climatic factors and anthropogenic activities (scenario-c), plus three additional scenarios that included climatic factors and anthropogenic activities but controlled for individual anthropogenic activities (scenario-d: grazing, scenario-e: collecting, and scenario-f: grazing and collecting). The results indicate that areas of suitable habitat for R. bieti are expected to decline by 8.0%–22.4% from 2000 to 2050, with the collection of local forest products and the grazing of domesticated cattle as the primary drivers of landscape fragmentation and range contraction. If these anthropogenic activities are strictly controlled, however, the area of suitable habitat is predicted to increase by10.4%–14.3%. We also found that habitats vulnerable to human disturbance were principally located in areas of low habitat connectivity resulting in limited migration opportunities and increased loss of genetic diversity among R. bieti living in these isolated subpopulations. Thus, we suggest that effective management policies to protect this species include prohibiting both livestock grazing and the collecting of forest products. Although our study focuses on a single primate species, the conservation modeling approaches we presented have wide applicability to a broad range of threatened mammalian and avian taxa that currently inhabit a limited geographic range and are affected by anthropogenic activities (e.g. collecting, grazing, hunting), loss of habitat connectivity, reduced genetic diversity, and the effects of climate change.